Intracranial hemorrhage after recombinant tissue plasminogen Activator: The competing risks survival analysis - Waitayaporn Pengtong; Natnaree Aimyong; Yongchai Nilanont (Interdisciplinary Neurosurgery, 2023)
Intravenous recombination of tissue plasminogen activator is a recommended treatment for patients with ischemic stroke. However, its side effects are associated with an increased risk of intracerebral hemorrhage. This study aimed to verify the factors associated with hemorrhagic transformation, classified by the clinical system, with time from onset to treatment. The medical records of patients with ischemic stroke who underwent recombination tissue plasminogen activator therapy at Siriraj Hospital, Thailand from October 2005 to June 2017 were included in this study. A sub-distribution hazard function by Fine-Gray model was applied to the data. Of the 241 records, 12.9 % presented with intracerebral hemorrhage, 4.6 % were symptomatic, and 8.3% were asymptomatic. The factors associated with increased risks of symptomatic intracerebral hemorrhage were older age (6.38–7.62 times higher than that compared with patients of younger age), high initial blood glucose (14.5 times higher), and systolic blood pressure (7.84 times higher). The factors associated with the asymptomatic type, in comparison with the risk of the symptomatic type, were older age (1.67–9.46 times higher than that compared with patients of younger stroke), higher stroke severity (1.39 times higher), and history of aspirin use (1.79 times higher). Modern technology and medical innovations cannot change the factors affecting intracranial hemorrhage. Screening methods for identifying hemorrhagic transformation after recombinant tissue plasminogen activator are important for patients with ischemic stroke.